Cost Escalation Issues in Construction Projects - Ahmed, Salman (Tropical Scientific Journal, 2023)
Objective: Cost escalations are a common issue, particularly in public projects which has significant effect on cost overrun. These escalations are caused by several factors which are important to control. This study identified various factors of cost escalation and assessed their level of significant. To complete the project successfully, it is imperative to identify these factors and then take the necessary steps to control or mitigate them. Research Method: Questionnaire survey was conducted for collecting data and analysis involved the weighted average method for raking the factors. Total 52 questionnaire forms were collected from client, consultant and contractors. Findings: Top five factors affecting cost escalation are that fluctuation in prices of construction materials, cash flow and financial difficulties faced, lack of decision making timely, slow payments and inflation. Originality: This study will help the practitioners to understand the significant issues which will help in controlling the cost escalation in construction projects